The The Influence of E-Service Quality on E-Customer Loyalty Through E-Satifcation as a Mediation in Indonesian Social Media Commerce - Efdison, Zefri; Lova, Anggil Nopra; Yadewani, Dorris; Harahap, Erni Febrina (The Future of Education Journal, 2024)
This research aims to determine the effect of e-service quality on e-customer loyalty mediated by e-satisfaction among social media commerce users in Indonesia. The sample of this research was 100 respondents. Data was collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used is descriptive analysis using SEM Amos 22. The results of the research show that there is a significant direct influence between e-service quality on e-satisfaction and e-customer loyalty among social media commerce users. There is a partial influence of the mediating impact of e-satisfaction between e-service quality on e-satisfaction and e-customer loyalty on social media commerce users. This shows that customer satisfaction can be built through good service so that customers do not switch to competitors.